SH.SEYITOV ROMANLARÍNDA METAFORALÍQ SÚWRETLEWDIŃ AYÍRÍM USÍLLARÍ - Sadenova, G.P. (ILIM hám JÁMIYET, 2024)
Active types of metaphorical meaning transfer methods are presented in the article, it’s features and it’s ability to be used in artistic text are studied on the example of the prose works of Shawdirbay Seyitov, a famous writer of the Karakalpak people.